2020
DOI: 10.1111/jnc.15216
|View full text |Cite
|
Sign up to set email alerts
|

Spatially resolved mass spectrometry analysis of amyloid plaque‐associated lipids

Abstract: Considered one of the biggest challenges of this century for pharmaceutical research and development, Alzheimer's Disease (AD), an incurable chronic neurodegenerative illness with no mechanism-based treatment options, is estimated to affect more than 40 million people around the globe (World Health Organization 2015).AD has a high financial and social burden, as cases are expected to double within the next 30 years, as our population ages.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 99 publications
(174 reference statements)
0
14
0
Order By: Relevance
“…It has been demonstrated the involvement of LysoPCs, PCs, Ceramides and Sphingomyelins in microglial inflammatory responses [51][52][53] . Particularly in AD, characteristic lipids, such as LysoPC(16:0), LysoPC(18:0), LysoPC(18:1) and Ceramides, were found associated with beta-amyloid plaques 54 . In like manner, these LysoPCs were also found up-regulated in a PD mouse model brain 55 .…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated the involvement of LysoPCs, PCs, Ceramides and Sphingomyelins in microglial inflammatory responses [51][52][53] . Particularly in AD, characteristic lipids, such as LysoPC(16:0), LysoPC(18:0), LysoPC(18:1) and Ceramides, were found associated with beta-amyloid plaques 54 . In like manner, these LysoPCs were also found up-regulated in a PD mouse model brain 55 .…”
Section: Discussionmentioning
confidence: 99%
“…A detailed review of the lipid content of these plaques, as identified through lipidomics studies, has recently been presented ( 58 ). In mouse models, relative to normal tissue, there is an accumulation of fatty acids, cholesterol, sulfatides, and phosphatidylethanolamine lipids in plaques, and a depletion of phosphatidylcholine (PC) lipids.…”
Section: Evidence For the Presence Of Lipids In Amyloid Fibrilsmentioning
confidence: 99%
“…Mass spectrometry is an important tool for probing biomolecular information in heterogeneous biological tissue. Localization, identification, and quantification of biomolecules in tissue sections by mass spectrometry can be achieved with imaging or by collection and off-line analysis of material from localized regions of interest (ROI). Mass spectrometry imaging excels at direct determination of the distribution of biomolecules within tissue sections with spatial resolution at micrometer scales. Mass spectrometry imaging (MSI) is rapid in part because it does not include a chromatographic separation step, but for this reason, quantification and identification are challenging.…”
Section: Introductionmentioning
confidence: 99%